The pledge ASA, peasant politics, and microfinance in the development of Bangladesh - Rutherford, Stuart (Oxford : Oxford University Press, 2009)
ASA of Bangladesh tops Forbes Magazine's list of the world's best microfinance banks. This book tells the story of how ASA's determined but practical-minded founder and leader, Shfiqual Haque Choudhury, steered his organisation through the maze of competing ideas about how best to develop poor countries.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Microfinance -- Bangladesh -- History; Peasants -- Bangladesh -- History; Rural poor -- Bangladesh -- History